Molecular characterization of fusion gene of recently isolated Newcastle disease virus isolates - Shahrestani, Kiarash Roohani; Ideris, Aini; Bejo, Mohd Hair; Tan, Sheau Wei; Yeap, Swee Keong; Pirozyan, Mehdi Rasoli; Jazayeri, Seyed Davoud; Goh, Su Hua; Omar, Abdul Rahman (2012)
Intensive vaccine programs have been implemented in many countries including Malaysia, but Newcastle disease virus (NDV) outbreaks have occurred, even in well-vaccinated farms. Hence, the present study was aimed to characterize five NDV isolates obtained from NDV vaccinated broiler farms in 2011 based on sequence and phylogenetic analysis of partial fusion gene. All the isolated NDV strains showed that they are categorized as velogenic NDV based on the presence of multi-basic protease cleavage sites, 112RRRKRF117. In addition, phylogenetic analysis showed that the isolates can classified under the genotype VII, subgenotype VIId.